Comprehensive definition of human immunodominant CD8 antigens in tuberculosis - Deborah A. Lewinsohn (Nature Portfolio, 2017)
Tuberculosis: Defining the proteins that drive immune responses Specific bacterial proteins have been found that drive effective immune responses to tuberculosis, with use in making more effective vaccines. Immunity to tuberculosis (TB) is facilitated by two types of white blood cell; however, most research has focused on one: the CD4+ T cell. Deborah A. Lewinsohn and David Lewinsohn, of the Oregon Health & Science University, USA, and collaborators lay out the essential functions of the oft-neglected CD8+ T cell, and undertook a broad approach to catalogue and define the bacterial proteins that activate the CD8+ T cell response. The team found that TB-infected humans reacted strongly to their protein library, and described several characteristics of CD8+ T cell ‘antigens’ (activators of immune cells) that will likely prove highly useful in the design of more protective TB vaccines.